DISPARITAS “HASIL PENGAWASAN APARAT PENGAWASAN INTERN PEMERINTAH” DALAM PENGUJIAN UNSUR PENYALAHGUNAAN WEWENANG - Awaludin Nur Ihfan; Shinta Hadiyantina; Riana Susmayanti (Faculty of Law, Parahyangan Catholic University, 2026)
The scope of the Administrative Court’s authority to examine elements of abuse of authority under Article 2 paragraph (2) of Supreme Court Regulation Number 4 of 2015 remains contentious, particularly regarding the interpretation of the phrase “APIP Supervision Results”. Divergent interpretations in judicial practice have generated legal uncertainty and affected access to legal protection for government officials seeking judicial review of alleged abuse of authority. This article examines the interpretive disparities surrounding the phrase and analyzes the implications of the diversity of supervisory mechanisms within Indonesia’s regulatory framework. With normative legal research using statutory, case, and conceptual approaches to examine relevant legislation, judicial decisions, and doctrinal perspectives concerning internal government supervision and administrative justice, the findings in this research indicate that differing judicial interpretive approaches have contributed significantly to legal uncertainty regarding the admissibility of petitions concerning abuse of authority. Moreover, the diversity of supervisory forms regulated in various laws demonstrates that interpretation based solely on the classification or form of supervision is inadequate. This study proposes a shift from a formalistic toward a substantive interpretive approach, whereby “APIP Supervision Results” are assessed based on the substance and objectives of the supervisory findings rather than their formal categorization. Therefore, it recommends vertical and horizontal harmonization of supervisory regulations to strengthen legal certainty and ensure effective legal protection for government officials through the mechanism for examining abuse of authority.